Management of Vicharchika (Eczema) by Multi-model Ayurveda Intervention: A Case Report - Shruti Prakash Kapatkar; Sourabh Deshmukh; Trupti Thakre; Renu Rathi (Journal of Clinical and Diagnostic Research, 2024)
Ayurveda, the ancient system of medicine, comprehensively categorises skin disorders under the term “Kushtharoga”, encompassing a wide spectrum of dermatological conditions. This classification is further elucidated into “Mahakushtha” and “Kshudra Kushtha”, representing major and minor skin diseases, respectively. Major skin ailments include psoriasis, eczema, leprosy, and vitiligo, while minor conditions encompass common issues such as acne and dermatitis. Vicharchika, a term in Ayurveda associated with symptoms akin to eczema, poses a challenge in contemporary medical practices, where treatment options are often limited to antihistamines and topical steroids. The present case report describes the successful Ayurvedic management of a patient presenting with complaints of itching, discharge and erythematous skin lesions on the foot. The 36-year-old female patient was diagnosed with Vicharchika (eczema) and received treatments such as Bahir Parimarjana Chikitsa (External treatment) and Shaman Chikitsa (alleviating treatment) in place of Shodhana (Purification therapy) due to Alpadoshaavastha (immature body tissues), which resulted in significant improvement. The present case underscores the potential efficacy of Ayurvedic interventions, emphasising the importance of personalised treatment strategies in addressing dermatological conditions.